Gedaanten van het realisme - Stedelijk museum, Leuven; Juwet, Willy; Duchateau, Marcel; Kint, J.; Bessemans, Lutgarde; Van Hove, R. (Leuven : Stedelijk Museum Leuven, 1982)
Albert, Jos ; De Marlier, Philippe ; Francis, George ; Gysbrechts, Cornelis ; Van Dorne, Frans ; Wiertz, Antoine ; Artan de Saint-Martin, Louis ; De Braekeleer, Henri ; Dubois, Louis ; Frederic, Leon ; Huberti, Edouard-Jules-Joseph ; Laudy, Jean ; etc.
Gedaanten van het Realisme, Stedelijk Museum Leuven, 25.9 - 25.11.1982
boek